Spatial Distribution of Highland Cattle in Alnus viridis Encroached Subalpine Pastures - Svensk, Mia; Pittarello, Marco; Nota, Ginevra; Schneider, Manuel K.; Allan, Eric; Mariotte, Pierre; Probo, Massimiliano (Frontiers in Ecology and Evolution, 2021)
Green alder (Alnus viridis) is a shrub species that has expanded over former pastures in Central Europe due to land abandonment, leading to negative agri-environmental impacts, such as a reduction in forage yield and quality and an increase in nitrate leaching. Robust livestock breeds such as Highland cattle could be used to control A. viridis encroachment. The objectives of this study were to investigate the impact of A. viridis encroachment on plant community composition and diversity and to map the spatial distribution of Highland cattle in A.viridis-encroached pastures. During the summer of 2019, three different Highland cattle herds were placed along an A.viridis encroachment gradient. A total of 58 botanical surveys were carried out before grazing to assess plant community composition, pastoral value and ecological indicator values. The spatial distribution of cattle was studied during the whole grazing period by monitoring 6 to 8 cows equipped with GPS collars in each herd. Plant species associated with higher pastoral values of the vegetation were found in areas with lower A.viridis cover, while highly encroached areas were dominated by a few nitrophilus and shade tolerant broad-leaved species and by ferns. Cattle spent more time in areas with higher pastoral value but did not avoid areas with high cover of A.viridis, on steep slopes or far from water. These results show that Highland cattle are able to tolerate harsh environmental conditions and that they can exploit A.viridis-encroached pastures. This suggests they have a high potential to reduce A. viridis encroachment in the long-term.